(untitled) (AmS-Skrifter, 2019)
The growth of gender archaeology has improved the inclusion of female and juvenile narratives in archaeological discourse, enabling us to better understand interactions between groups defined by both social and physiological differences. There has been a notable absence of elderly in research, however, that is not simply a question of attitudes but of methodological limitations. The emergence of biostatistics has offered novel ways to combat common issues such as age mimicry and avoid the problematic nature of culturally loaded descriptive terminology. A test performed on Transition Analysis by Boldsen et al. (2002), generates individual age estimates, which allow for better differentiation between individuals and age groups, such as the ‘45+ older adults’. Further research into biostatistical methods will not only improve objectivity but bring much-needed attention to the elderly, including their narrative into the investigation of family dynamics and adult-juvenile interactions.